Canva-Based Moral Psychomotor Assessment Model At Smpit Assyifa Boarding School Wanareja Subang - Hafidin Nurhadi; Ani Fatimah Zahra Saifi; Erik Jaenudin; Badrudin Badrudin; Qiqi Yuliati Zaqiyah (Journal on Education, 2024)
The subject of Akidah Akhlak is a very important subject to be taught to students. The values of the Akidah Akhlak subject are needed to be practiced in everyday life. Through the subject of Akidah Akhlak, students are taught about how to behave / have good morals based on Islamic teachings. This study aims to analyze the design of the Canva-based moral assessment model, the effectiveness of the Canva-based moral assessment model in Akidah Akhlak learning and the challenges and opportunities in implementing the Canva-based moral assessment model at SMPIT As-Syifa Wanareja Subang. This research is a type of research with a qualitative and quantitative approach (mix methods), using a sequential exploratory strategy, namely in the first stage collecting and analyzing qualitative data then the second stage collecting and analyzing quantitative data. The primary data used is data from the field or what is called field research. The secondary data comes from books and articles in scientific journals related to the discussion. The results of this study reveal that the Canva-based assessment model design is an alternative for teachers in choosing the right assessment, the Canva-based psychomotor assessment model in Akidah Akhlak learning at SMPIT Assyifa Boarding School Wanareja Subang is effective and has significant challenges and opportunities.